Upregulation of microRNA-125b-5p alleviates acute liver failure by regulating the Keap1/Nrf2/HO-1 pathway - Tao, Ya-Chao; Wang, Yong-Hong; Wang, Meng-Lan; Jiang, Wei; Wu, Dong-Bo; Chen, En-Qiang; Tang, Hong (Frontiers in Immunology, 2022)
Background Acute liver failure (ALF) and acute-on-chronic liver failure (ACLF) are the two most common subtypes of liver failure. They are both life-threatening clinical problems with high short-term mortality. Although liver transplantation is an effective therapeutic, its application is limited due to the shortage of donor organs. Given that both ACLF and ALF are driven by excessive inflammation in the initial stage, molecules targeting inflammation may benefit the two conditions. MicroRNAs (miRNAs) are a group of small endogenous noncoding interfering RNA molecules. Regulation of miRNAs related to inflammation may serve as promising interventions for the treatment of liver failure. Aims To explore the role and mechanism of miR-125b-5p in the development of liver failure. Methods Six human liver tissues were categorized into HBV-non-ACLF and HBV-ACLF groups. Differentially expressed miRNAs (DE-miRNAs) were screened and identified through high-throughput sequencing analysis. Among these DE-miRNAs, miR-125b-5p was selected for further study of its role and mechanism in lipopolysaccharide (LPS)/D-galactosamine (D-GalN) -challenged Huh7 cells and mice in vitro and in vivo. Results A total of 75 DE-miRNAs were obtained. Of these DE-miRNAs, miR-125b-5p was the focus of further investigation based on our previous findings and preliminary results. We preliminarily observed that the levels of miR-125b-5p were lower in the HBV-ACLF group than in the HBV-non-ACLF group. Meanwhile, LPS/D-GalN-challenged mice and Huh7 cells both showed decreased miR-125b-5p levels when compared to their untreated control group, suggesting that miR-125b-5p may have a protective role against liver injury, regardless of ACLF or ALF. Subsequent results revealed that miR-125b-5p not only inhibited Huh7 cell apoptosis in vitro but also relieved mouse ALF in vivo with evidence of improved liver histology, decreased alanine aminotransferase (ALT) and aspartate aminotransferase (AST) levels, and reduced tumor necrosis factor-α (TNF-α) and IL-1β levels. Based on the results of a biological prediction website, microRNA.org, Kelch-like ECH-associated protein 1 (Keap1) was predicted to be one of the target genes of miR-125b-5p, which was verified by a dual-luciferase reporter gene assay. Western blot results in vitro and in vivo showed that miR-125b-5p could decrease the expression of Keap1 and cleaved caspase-3 while upregulating the expression of nuclear factor (erythroid-derived 2)-like 2 (Nrf2) and heme oxygenase-1(HO-1). Conclusion Upregulation of miR-125b-5p can alleviate acute liver failure by regulating the Keap1/Nrf2/HO-1 pathway, and regulation of miR-125b-5p may serve as an alternative intervention for liver failure.